The definition of complementary angles is that the sum of their measures is equal to 90 degrees. Therefore, we have the equation:
(x+2) + (2x - 4) = 90
Simplifying the equation, we have:
3x - 2 = 90
Adding 2 to both sides of the equation, we get:
3x = 92
Dividing both sides of the equation by 3, we have:
x = 92/3
So the written equation is:
(x+2) + (2x - 4) = 90
A figure displays two nonadjacent angles with measures (x+2)° and (2x−4)° . If the two angles are complementary, what is the written equation?
11 answers
A figure displays two adjacent complementary angles with measures (x+3)° and (4x−2)° . What is the equation of the angles measures?
The definition of complementary angles is that the sum of their measures is equal to 90 degrees. Therefore, we have the equation:
(x+3) + (4x - 2) = 90
Simplifying the equation, we have:
5x + 1 = 90
Subtracting 1 from both sides of the equation, we get:
5x = 89
Dividing both sides of the equation by 5, we have:
x = 89/5
So the equation of the angle measures is:
(x+3) + (4x - 2) = 90
(x+3) + (4x - 2) = 90
Simplifying the equation, we have:
5x + 1 = 90
Subtracting 1 from both sides of the equation, we get:
5x = 89
Dividing both sides of the equation by 5, we have:
x = 89/5
So the equation of the angle measures is:
(x+3) + (4x - 2) = 90
What is the equation for determining the angle measures?
The equation for determining the angle measures of two adjacent complementary angles is:
(x+3) + (4x-2) = 90
(x+3) + (4x-2) = 90
two complementary angles have measures (4x)° and (2x)° . What is the value of x and the two angle measures?
According to the definition of complementary angles, the sum of their measures is equal to 90 degrees. Therefore, we have the equation:
(4x) + (2x) = 90
Simplifying the equation, we have:
6x = 90
Dividing both sides of the equation by 6, we get:
x = 15
Now we can substitute the value of x back into the expressions of the angle measures to find their values.
The first angle measure is (4x)° = 4(15)° = 60°.
The second angle measure is (2x)° = 2(15)° = 30°.
So, the value of x is 15 and the two angle measures are 60° and 30°.
(4x) + (2x) = 90
Simplifying the equation, we have:
6x = 90
Dividing both sides of the equation by 6, we get:
x = 15
Now we can substitute the value of x back into the expressions of the angle measures to find their values.
The first angle measure is (4x)° = 4(15)° = 60°.
The second angle measure is (2x)° = 2(15)° = 30°.
So, the value of x is 15 and the two angle measures are 60° and 30°.
In a figure, one complementary angle has a measure of 36° and the other has a measure of (x−3)° . What is the value of x and the value of the unknown angle measure?
According to the definition of complementary angles, the sum of their measures is equal to 90 degrees. Therefore, we have the equation:
36 + (x-3) = 90
Simplifying the equation, we have:
x - 3 = 90 - 36
x - 3 = 54
Adding 3 to both sides of the equation, we get:
x = 57
So, the value of x is 57.
To find the value of the unknown angle measure, we substitute x=57 back into the expression (x-3)°:
(x-3)° = (57-3)° = 54°
So, the value of the unknown angle measure is 54°.
36 + (x-3) = 90
Simplifying the equation, we have:
x - 3 = 90 - 36
x - 3 = 54
Adding 3 to both sides of the equation, we get:
x = 57
So, the value of x is 57.
To find the value of the unknown angle measure, we substitute x=57 back into the expression (x-3)°:
(x-3)° = (57-3)° = 54°
So, the value of the unknown angle measure is 54°.
1. (x + 2) + (2x - 4) = 90
2. (x + 3) + (4x - 2) = 90
3. (7x - 9) + 4x = 90
4. x = 15, (4x) = 60, and (2x) = 30
5. x = 57, unknown angle measure = 54
Btw I am the same person from the last quick check and practice answers!
I'm glad I could help!
2. (x + 3) + (4x - 2) = 90
3. (7x - 9) + 4x = 90
4. x = 15, (4x) = 60, and (2x) = 30
5. x = 57, unknown angle measure = 54
Btw I am the same person from the last quick check and practice answers!
I'm glad I could help!
The answers for the quick check are already posted by someone else so search up the first questions to find it!